(untitled) (Моделювання, керування та інформаційні технології, 2025)
Дослідження присвячено узагальненню числового методу комплексного аналізу моделювання процесів повільного руху води в водоймах, обмежених лініями втоку, витоку та береговими непроникними лініями. При цьому розглядаються різні варіанти формування течії в залежності від величин керуючих параметрів (граничних потенціалів, витрат тощо). The research is devoted to the generalization of the numerical method of the complex analysis of modeling the processes of slow movement of water in reservoirs limited by the lines of inflow, outflow and coastal impervious lines. At the same time, various options for the formation of the current are considered depending on the values ​​of the control parameters (potentials on the borders, expenses, etc.).